(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
This article proposes a contribution to a methodological and theoretical discussion in contemporary film studies: how to study and teach cinema cultures in the age of globalization? In a first step, the approach to World Literature proposed by literary scholar Franco Moretti is re-visited and discussed in terms of its productivity and limitations. The article then asks if cinematic traditions can be understood in a comparative perspective, as the result of processes of mutual exchange, circulation and friction beyond the confines of a paradigm of national cinema, and along pathways of circulation not necessarily shaped and controlled by the supposedly inevitable forces of Western capitalism. Commercial Hindi cinema is used as a case study – the article in particular discusses the temporal-spatial constellation of Pakeezah (Pure One, Kamal Amrohi, 1972).